Computer-Based and Paper-Based Reading Comprehension in Adolescents With Typical Language Development and Language-Learning Disabilities. (Language, Speech & Hearing Services in Schools, 2012)
Purpose: With the global expansion of technology, our reading platform has shifted from traditional text to hypertext, yet little consideration has been given to how this shift might help or hinder students' reading comprehension. The purpose of this study was to compare reading comprehension of computer-based and paper-based texts in adolescents with and without language-learning disabilities (LLD). Method: Fourteen adolescents with LLD and 25 adolescents with typical language development (TLD) read literary texts in computer-based and paper-based formats and then answered reading comprehension questions. Results: The LLD group scored significantly lower than the TLD group on the reading comprehension measure, but there were no significant between-group differences for reading or answering time. In addition, there were no significant within-group differences for the computer-based or paper-based conditions. Predictors for reading comprehension varied by group and condition. Conclusion: Neither group appeared to be affected by the additional cognitive load imposed by hypertext in the computer-based condition; however, the load between conditions may not have been sufficient to differentially impact reading comprehension. Based on the regression analyses, it appears that working memory, oral language, and decoding differed in their contribution to reading comprehension for each group and condition.